Oregano Extract Added into the Diet of Dairy Heifers Changes Feeding Behavior and Concentrate Intake - Giovani Jacob Kolling; Dejani Maíra Panazzolo; Alexandre Mossate Gabbi; Marcelo Tempel Stumpf; Marcel Batista dos Passos; Eduardo Augusto da Cruz; Vivian Fischer (The Scientific World Journal)
This experiment aimed to describe the effects of Oregano extract (OE) inclusion into the concentrate fed to dairy heifers on physiological parameters, feeding behavior, intake, and performance. Thirty-two Holstein heifers were randomly distributed into four treatments: C = control, without addition of OE; OE2.5 = 2.5 g; OE5.0 = 5.0 g and OE7.5 = 7.5 g of Oregano extract per heifer/day. Feeding behavior and concentrate intake were assessed individually every day and total dry matter intake (DMI) was determined on the last week of the trial. Compared to control group, OE7.5 reduced by 32% the latency time to approach the feed bunk but increased by 6% the time spent eating the concentrate. Each inclusion of 2.5 grams of OE into the concentrate increased the occurrence of postingestive licking the feed bunk with abundant saliva production 1.2 times (P<0.01) and tended to increase the occurrence of sneeze events 1.2 times (P<0.10). No statistical difference was detected between treatments for total DMI, but concentrate DMI was 9% lower for OE7.5 when compared to control and OE2.5. The inclusion of 7.5 grams/day of OE causes small but negative effects in feeding behavior and concentrate intake, without change on total dry matter intake.